Community pharmacy-led diabetes management using continuous glucose monitoring for suboptimally controlled type 2 diabetes: A pilot feasibility study - Kyung-In Joung; Ji Won Hwang; So Young Seo; Kyeong Han Back; Yong Geun Jeon; Kwang Joon Kim (PLoS ONE, 2026)
Many adults with type 2 diabetes mellitus (T2DM) managed without insulin continue to experience suboptimally controlled glycemia. This 12-week, single-arm pilot feasibility study was conducted across 11 community pharmacies in South Korea to evaluate the feasibility and clinical effectiveness of a community pharmacy-led diabetes management model using continuous glucose monitoring (CGM) integrated with digital health platforms. Thirty adults with suboptimally controlled T2DM (HbA1c ≥ 6.5%) on stable oral regimens were enrolled. The intervention combined medication, exercise, and nutrition counseling using CGM (Abbott LibreView®) integrated with the national Personal Health Record system. The primary composite endpoint was defined as achieving all three at week 12: (1) HbA1c ≤ 7.0%, (2) meaningful HbA1c reduction (≥0.5% absolute or ≥10% relative), and (3) time in range (TIR, 70–180 mg/dL) >70%. Results showed that all 30 participants completed the program, with 36.7% achieving the primary composite endpoint. At week 12, HbA1c decreased by 0.70% (95% CI: –1.00 to –0.39; p < 0.001), TIR increased by 5.8 percentage points (p < 0.001), and time above range declined. Time below range remained stable, confirming safety. Improvements appeared from week 3 and were sustained, with longer diabetes duration independently predicting response (adjusted OR=1.24/year, p = 0.040). In conclusion, community pharmacy-led diabetes management using CGM, enabled by digital health integration, produced clinically meaningful and sustained glycemic improvements among adults with T2DM not using insulin. (Trial Registration: KCT0010933).